How Do Top Acquirers Compare in Technology Mergers? New Evidence from an S&P Taxonomy - Jin, Ginger Zhe,Leccese, Mario,Wagman, Liad (National Bureau of Economic Research, 2022)
Some argue that large platforms, such as Alphabet/Google, Amazon, Apple, Facebook and Microsoft (or GAFAM), are unusual in their number, pace and concentration of technology mergers, with the potential to harm market competition. Using a unique taxonomy developed by S&P Global Market Intelligence, we compare the M&A activities of GAFAM to other top acquirers from 2010 to 2020. We find: (i) GAFAM completed more tech acquisitions per firm than other groups of top acquirers, and acquired younger and more consumer-facing firms on average. (ii) The top 25 private equity firms outpaced GAFAM in tech acquisitions per firm since 2018. (iii) GAFAM acquisitions are less concentrated across tech categories than other top acquirer groups, due, in part, to an
10.3386/w29642
Keywords: Arbeitspapier; Graue Literatur; Großunternehmen; IKT-Sektor; Innovationsmanagement; Übernahme; Wettbewerb; Aktienindex; S&P 500; Big Tech; GAFAM; Schätzung; Wirkungsanalyse